[tex](2x-3y)(4x^2+6xy+9y^2)[/tex] is the factored form of [tex]8x^3-27y^3[/tex]
Solution:
We have to factor the given expression
[tex]8x^3-27y^3[/tex]
We can use the algebraic identity to factor the given expression
[tex]a^3-b^3=(a-b)(a^2+ab+b^2)[/tex]
Lets make the given expression in form of [tex]a^3-b^3[/tex]
[tex]8x^3-27y^3=(2)^3(x)^3-(3)^3(y)^3[/tex]
[tex]8x^3-27y^3=(2x)^3-(3y)^3[/tex]
Now apply the algebraic property in above expression
Here, a = 2x and b = 3y
Therefore,
[tex](2x)^3-(3y)^3=(2x-3y)((2x)^2+(2x)(3y)+(3y)^2)[/tex]
[tex](2x)^3-(3y)^3=(2x-3y)(4x^2+6xy+9y^2)[/tex]
Thus the given expression is factored out